Increasing Student Learning Motivation in Mathematics Learning: Literatur Review - Rahayu, Sri; Warsinih, Wiwin; Rasilah, Rasilah (MASI Mandiri Edukasi, 2024)
Motivation is a crucial factor influencing student performance in the Mathematics learning process. This research aims to identify strategies to enhance student motivation in Mathematics, addressing the common issue of low enthusiasm and reduced classroom activity. The objective is to develop effective teaching methods that increase student perseverance and independent learning in Mathematics. The study applied a mixed-methods approach, combining quantitative surveys to measure student motivation levels and qualitative interviews with teachers to explore successful motivational strategies. Data was collected from 200 high school students and 20 Mathematics teachers in Jakarta. Statistical analysis was used to identify significant factors affecting Motivation, while thematic analysis provided insights into effective teaching practices. The results indicate interactive teaching methods, personalized feedback, and real-world problem-solving activities significantly boost student motivation. Students reported higher engagement and better performance when these strategies were implemented. The study concludes that adopting these methods can effectively address low Motivation in Mathematics, improving student outcomes.